A Polyborate Coated Cellulose Composite Separator for High Performance Lithium Ion Batteries. Issue 6 (1st January 2015) - Ding, Guoliang; Qin, Bingsheng; Liu, Zhihong; Zhang, Jianjun; Zhang, Bo; Hu, Pu; Zhang, Chuanjian; Xu, Gaojie; Yao, Jianhua; Cui, Guanglei
Abstract : In this paper, a single ion polymer electrolyte enhanced cellulose nonwoven separator has been successfully explored via a dip-coating process for high-performance lithium ion battery. The single ion polymer electrolyte was comprised of polymeric lithium tartaric acid borate salt (PLTB) and polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP). This single ion polymer electrolyte enhanced cellulose composite separator exhibited higher ionic conductivity, good flame retardancy and superior thermal resistance compared to the commercial polypropylene (PP) separator. Moreover, the composite separator at room temperature possessed lithium ion transference number (tLi + ) of 0.48, which was higher than that using the pristine cellulose nonwoven (0.31). Furthermore, it was demonstrated that the lithium cobalt oxide (LiCoO2 )/graphite cell with the composite separator delivered superior rate capability and better cycling performance than those with PP separator. These fascinating characteristics would endow this composite nonwoven a promising separator for high-performance lithium ion battery.